Improvement of Several Chemical Properties of Ultisols Using a Mixed Compost of Chicken Manure and Leucaena leucocephala - Krismon Sujati; wiskandar jakhtar; Najla Anwar Fuadi (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2026)
Ultisols is a soil type characterized by low fertility, particularly deficient in phosphorus (P), which is essential for plant growth. Organic amendments, such as compost, have the potential to improve soil nutrient availability. This study aimed to analyze the effect of applying a mixed compost of chicken manure and Leucaena leucocephala on several chemical properties of Ultisols. The experiment was conducted from February to July 2023 in Simpang Sungai Duren Village, Jambi Luar Kota District, Muaro Jambi Regency. A Randomized Complete Block Design (RCBD) with six treatments and four replications was used, resulting in 24 experimental plots. The treatments consisted of different application rates of compost made from a mixture of chicken manure and Leucaena leaves, namely 0, 5, 10, 15, 20, and 25 tons ha⁻¹, applied 15 days before planting. The results indicated that the compost derived from chicken manure and Leucaena leaves significantly increased the available P content in Ultisols compared with the control treatment. The highest available P content was obtained at the highest compost application rate, which increased available phosphorus by 1245% compared to the control. In addition, compost application improved several soil chemical properties, including an increase in soil pH by 28.2% and soil organic matter content by 38%, which contributed to the enhanced availability of phosphorus in the soil. The compost mixture of chicken manure and Leucaena leaves proved effective in increasing the availability of phosphorus in Ultisols, offering a potential strategy for improving crop productivity in nutrient-poor soils. Keywords: compost, soil chemistry, soybeans, Ultisols